Life-course BMI and biomarkers in persons aged 60 years or older: a comparison of the USA and Costa Rica - Rehkopf, David H. (2019)
Objective: There is a large literature linking current body mass index (BMI) to levels of cardiovascular risk biomarkers, but it is unknown whether measures of BMI earlier in the life course and maximum BMI are predictive of current levels of biomarkers. The objective of this study is to determine how current, maximum and age 25 body mass index among individuals over the age of 60 are associated with their current levels of cardiovascular risk biomarkers. Design: Cross-sectional study with retrospective recall. Setting: Costa Rica (n=821) and the United States (n=4110). Subjects: Nationally representative samples of adults aged 60 and over. Results: We used regression models to examine the relationship between multiple meaures of body mass index with four established cardiovascular risk biomarkers. The most consistent predictor of current levels of systolic blood pressure, triglycerides and HDL cholesterol is current BMI. However, maximum BMI is the strongest predictor of hemoglobin A1c and is also related to HDL cholesterol and triglycerides. Hemoglobin A1c is independent of current BMI. We find that these relationships are consistent between Costa Rica and the United States for hemoglobin A1c and for HDL cholesterol. Conclusions: Current levels of cardiovascular risk biomarkers are not only the product of current levels of BMI, but also of maximum lifetime BMI, in particular for levels of hemoglobin A1c and for HDL cholesterol. Managing maximum obtained BMI over the life course may be most critical for maintaining the healthiest levels of cardiovascular risk.